HDAC inhibition in glioblastoma monitored by hyperpolarized 13C MRSI. (18th December 2018) - Radoul, Marina; Najac, Chloé; Viswanath, Pavithra; Mukherjee, Joydeep; Kelly, Mark; Gillespie, Anne Marie; Chaumeil, Myriam M.; Eriksson, Pia; Delos Santos, Romelyn; Pieper, Russell O.; Ronen, Sabrina M.
Abstract : Vorinostat is a histone deacetylase (HDAC) inhibitor that inhibits cell proliferation and induces apoptosis in solid tumors, and is in clinical trials for the treatment of glioblastoma (GBM). The goal of this study was to assess whether hyperpolarized 13 C MRS and magnetic resonance spectroscopic imaging (MRSI) can detect HDAC inhibition in GBM models. First, we confirmed HDAC inhibition in U87 GBM cells and evaluated real‐time dynamic metabolic changes using a bioreactor system with live vorinostat‐treated or control cells. We found a significant 40% decrease in the 13 C MRS‐detectable ratio of hyperpolarized [1‐ 13 C]lactate to hyperpolarized [1‐ 13 C]pyruvate, [1‐ 13 C]Lac/Pyr, and a 37% decrease in the pseudo‐rate constant, k PL, for hyperpolarized [1‐ 13 C]lactate production, in vorinostat‐treated cells compared with controls. To understand the underlying mechanism for this finding, we assessed the expression and activity of lactate dehydrogenase (LDH) (which catalyzes the pyruvate to lactate conversion), its associated cofactor nicotinamide adenine dinucleotide, the expression of monocarboxylate transporters (MCTs) MCT1 and MCT4 (which shuttle pyruvate and lactate in and out of the cell) and intracellular lactate levels. We found that the most likely explanation for our finding that hyperpolarized lactate is reduced in treated cells is a 30% reduction in intracellular lactate levels that occurs as a result of increased expression of both MCT1 and MCT4 in vorinostat‐treated cells. In vivo 13 C MRSI studies of orthotopic tumors in mice also showed a significant 52% decrease in hyperpolarized [1‐ 13 C]Lac/Pyr when comparing vorinostat‐treated U87 GBM tumors with controls, and, as in the cell studies, this metabolic finding was associated with increased MCT1 and MCT4 expression in HDAC‐inhibited tumors. Thus, the 13 C MRSI‐detectable decrease in hyperpolarized [1‐ 13 C]lactate production could serve as a biomarker of response to HDAC inhibitors. Abstract : In this study we used 13 C MRSI and hyperpolarized [1‐ 13 C]pyruvate to monitor GBM response to HDAC inhibition by Vorinostat. We first monitored the effect of Vorinostat in live cells and then in orthotopic GBM xenografts in mice. We found that in both cell and animal studies inhibition of HDAC with Vorinostat led to a decrease in hyperpolarized [1‐ 13 C]lactate to hyperpolarized [1‐ 13 C]pyruvate ratio [1‐ 13 C]Lac/Pyr. Our study highlights the potential of using hyperpolarized 13 C MRSI for monitoring HDAC inhibition in GBM patients.